2018
DOI: 10.1159/000487144
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Benzaldehyde, Vanillin, Muscone and Borneol on P-Glycoprotein in Caco-2 Cells and Everted Gut Sac

Abstract: Aims: In clinical practice, herbal medicines have played an important role in the modulation of drug transporters through the combination of conventional prescription drugs, which necessitates the elucidation of herb-drug interactions. The present study was designed to investigate the inhibitory effects and mechanisms of benzaldehyde, vanillin, muscone, and borneol on P-glycoprotein (P-gp). Methods: The effects of the 4 compounds on the intracellular accumulation of rhodamine-123 (Rho-123) in vinblastine-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It is a simple, fast, economic, and reproducible method for predicting drug permeability and evaluating the performance of drug delivery systems (Wang et al. 2018 ). The ex vivo rat permeation profile and intestinal apparent permeability results were presented in Figure 6(B) and Figure 6(C) .…”
Section: Resultsmentioning
confidence: 99%
“…It is a simple, fast, economic, and reproducible method for predicting drug permeability and evaluating the performance of drug delivery systems (Wang et al. 2018 ). The ex vivo rat permeation profile and intestinal apparent permeability results were presented in Figure 6(B) and Figure 6(C) .…”
Section: Resultsmentioning
confidence: 99%
“…He et al [10] suggested that borneol inhibits the P-gp-mediated efflux system, and thereby improves the intestinal absorption of drugs. Wang et al [33] reported that borneol increases the absorption rate and apparent permeability coefficient of Rho-123 in the rat jejunum and ileum.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase consisted of a solution of acetonitrile and water at a ratio of 35:65. The flow rate of mobile phase was 0.8 mL/min ( Wang et al., 2018 ). The apparent permeability coefficient ( P app ) of Rho-123 across Caco-2 cells was calculated according to Eq.…”
Section: Methodsmentioning
confidence: 99%